Fibroblast growth factor 9 (FGF9) inhibits myogenic differentiation of C2C12 and human muscle cells. Issue 24 (17th December 2019) - Huang, Jian; Wang, Kun; Shiflett, Lora A.; Brotto, Leticia; Bonewald, Lynda F.; Wacker, Michael J.; Dallas, Sarah L.; Brotto, Marco
ABSTRACT: Osteoporosis and sarcopenia (osteosarcopenia (OS)) are twin-aging diseases. The biochemical crosstalk between muscle and bone seems to play a role in OS. We have previously shown that osteocytes produce soluble factors with beneficial effects on muscle and vice versa . Recently, enhanced FGF9 production was observed in the OmGFP66 osteogenic cell line. To test its role in myogenic differentiation, C2C12 myoblasts were treated with recombinant FGF9. FGF9 as low as 10 ng/mL inhibited myogenic differentiation, suggesting that FGF9 might be a potential inhibitory factor produced from bone cells with effects on muscle cells. FGF9 (10–50 ng/mL) significantly decreased mRNA expression of MyoG and Mhc while increasing the expression of Myostatin . Consistent with the phenotype, RT-qPCR array revealed that FGF9 (10 ng/mL) increased the expression of Icam1 while decreased the expression of Wnt1 and Wnt6 decreased, respectively. FGF9 decreased caffeine-induced Ca 2+ release from the sarcoplasmic reticulum (SR) of C2C12 myotubes and reduced the expression of genes (i.e. Cacna1s, RyR2, Naftc3 ) directly associated with intracellular Ca 2+ homeostasis. Myogenic differentiation in human skeletal muscle cells was similarly inhibited by FGF9 but required higher doses of 200 ng/mL FGF9. FGF9 was also shown to stimulate C2C12 myoblast proliferation. FGF2 and the FGF9 subfamily members FGF16 and FGF20 also inhibited C2C12 myoblast differentiation and enhanced proliferation. Intriguingly, the differentiation inhibition was independent of proliferation enhancement. These findings suggest that FGF9 may modulate myogenesis via a complex signaling mechanism.